Bioresorbable vascular scaffold use for coronary bifurcation lesions: A substudy from GHOST EU registry. Issue 1 (14th July 2016) - Naganuma, Toru; Colombo, Antonio; Lesiak, Maciej; Capodanno, Davide; Gori, Tommaso; Nef, Holger; Caramanno, Giuseppe; Naber, Christoph; Di Mario, Carlo; Ruparelia, Neil; Capranzano, Piera; Wiebe, Jens; et al.
Abstract : Objectives: The aim of this study was to evaluate midterm outcomes of bioresorbable vascular scaffolds (BVS) implanted in bifurcation lesions. Background: BVS have emerged as an alternative to conventional metallic drug‐eluting stents for the treatment of coronary complex lesions. Methods: Between November 2011 and January 2014, 1189 patients underwent percutaneous coronary intervention with BVS at 10 European centers (GHOST EU registry). Of these, 289 consecutive patients (302 bifurcation lesions) treated with either single‐stenting ( n = 260) or double‐stenting ( n = 42) were evaluated. Results: True bifurcations were treated in 44.7%. Intravascular ultrasound and optical coherence tomography were utilized only in 22.2% and 21.2%, respectively. Predilation was performed in 95.4%, while postdilation of the main branch was performed in 61.3%. Final kissing inflation with no or minimal protrusion of a side‐branch balloon into main branch was performed in 18.9%. Median follow‐up period was 356 (IQR 191–419) days. The Kaplan–Meier estimated rates of target lesion failure and scaffold thrombosis (ST) were 6.4% and 2.5% at 360 days, respectively. Independent predictors for TLF were ACS and diabetes mellitus (HR 4.67; 95% CI: 1.78–12.3; P = 0.002 and HR 3.37; 95% CI: 1.38–8.26; P = 0.008, respectively). Conclusions: BVS use for coronary bifurcation lesions in an "all‐comer" population was associated with acceptable TLF rates up to midterm follow‐up. However, ST rates were higher than seen with contemporary metallic stents possibly due to the low incidence of intravascular guidance and postdilation resulting in a higher likelihood of scaffold underexpansion and malapposition, further supporting the importance of meticulous implantation technique. © 2016 Wiley Periodicals, Inc.